Sustainability and environmental management practices from consumer perspective - Rutanen, Arttu (My University, 2022)
Sustainability is something that cannot be avoided nowadays and discussions around it can be fierce. Companies are implementing different types of environmental managements systems to improve the sustainability of their operations. Consumers are being informed by variety of sustainability information sources and the reliability of that information is not always as it seems. This thesis studies how consumers perceive those sustainability and environmental management practices that companies are doing. It is also helping to identify how sustainability influences consumer behavior and how consumers see the sustainability communication. This thesis is also aiming to explain how sustainability and environmental management practices are used. The aim of this research is to find out how consumer sees the sustainability and environmental management actions. Popularity of research around sustainability is increasing, but as the area of sustainability constantly changes, there is need for continuous research. Usually researches about sustainability have been about the environmental impacts of different aspects that have effect on sus-tainability. This research is based on quantitative data that was received from the questionnaire, which was conducted by third-party company. There were 500 valid respondents for the questionnaire, which represent Finnish consumer base. The questionnaire was constructed around the theoretical framework from the literature review. Literature review includes three main parts, which are sustainability, environmental management and consumer behavior. In addition to the literature review, this study includes short introduc-tion of the case company Eckes-Granini Finland Oy Ab and its sustainability and environ-mental practices. The questionnaire results were analyzed by descriptive statistic and sta-tistical analysis, which includes Pearson Chi-Square test and two-tailed test of significance. Those statistical tests measure association between two different factors. The results of this study identified consumer perceptions of sustainability and environmental management practices. The results revealed that those perceptions differ based on the gender, age and region of consumers. Results identified how sustainability affects the consumer behavior and how consumers experience the sustainability communication. Those are also differing based on gender, age and region of consumers. The findings from the literature illustrate that Finnish food industry companies are continuously working towards being more sustainable. Results of this study can be used to improve the knowledge of consumers about sustainability and environmental management. Based on the findings of this study, different types of sustainability information can be better di-rected to identified groups of consumers. These results are also helping companies to predict the effect of sustainability to consumer behavior.

Vastuullisuudesta on tullut asia, jolta ei voi välttyä nykypäivänä ja keskustelut sen ympärillä voivat olla usein kiihkeitäkin. Yritykset ottavat ja ovat ottaneet käyttöön erilaisia ympäristöjohtamisen järjestelmiä parantaakseen toimiensa vastuullisuutta. Kuluttajille tuotetaan vaihtelevalla kirjolla tietoa vastuullisuudesta erilaisista lähteistä, joiden luotettavuutta ei pystytä takamaan. Tämä tutkielma tutkii kuinka kuluttajat näkevät yrityksien vastuullisuuden ja ympäristöjohtamisen käytännöt. Tutkielma auttaa myös tunnistamaan miten vastuullisuus vaikuttaa kuluttajakäyttäytymiseen ja miten kuluttajat näkevät vastuullisuusviestinnän. Lisäksi tutkielma pyrkii selvittämään miten vastuullisuuden ja ympäristöjohtamisen keinoja käytetään. Tämän tutkimuksen tavoitteena on selvittää, kuinka kuluttajat käsittävät vastuullisen ja ympäristöjohtamisen käytännöt. Vastuullisuuteen liittyvien tutkimusten suosio tulee kasvamaan, ja koska vastuullisuus kehittyy jatkuvasti, uusille tutkimuksille on jatkuva tarve. Useimmiten vastuullisuustutkimukset liittyvät ympäristövaikutuksiin ja eri tekijöiden vaikutuksiin. Tutkimus perustuu kvantitatiiviseen dataan, joka saatiin kolmannen osapuolen toteuttamasta kyselystä. Aineistoin koko oli 500 tutkimukseen sopivaa vastaajaa, jotka edustivat Suomen kuluttajia. Kysely tehtiin kirjallisuuskatsaukseen teoriaan perustuen, joka sisältää kolme pääteemaa: vastuullisuuden, ympäristöjohtamisen ja kuluttajakäyttäytymisen. Kirjallisuuskatsauksen lisäksi tutkimus sisältää lyhyen esittelyn case-yrityksestä Eckes-Granini Finland Oy Ab ja sen vastuullisuudesta ja ympäristöjohtamisen käytännöistä. Kyselyn tulokset analysoitiin tilastollisen kuvailun ja tilastollisen analyysin keinoja käyttäen, johon kuuluvat Khiin neliön –riippumattomuustesti ja kaksisuuntainen riippumattomuustesti. Kyseiset testit mittaavat kahden tekijän välistä tilastollista riippuvuutta. Tutkimuksen tulokset tunnistavat kuluttajien käsityksiä yrityksien vastuullisuudesta ja ympäristöjohtamisen käytännöistä. Tulokset paljastavat, että kyseisiin käsityksiin vaikuttavat kuluttajien sukupuoli, ikä ja asuinalue. Tulokset tunnistavat kuinka vastuullisuus vaikuttaa kuluttajakäyttäytymiseen ja miten kuluttajat kokevat vastuullisuuteen liittyvän viestinnän. Kuluttajien sukupuoli, ikä ja asuinalue vaikuttavat myös näihin vastauksiin. Kirjallisuuskatsauksessa käytiin läpi lisäksi Suomen elintarviketeollisuuden yritysten jatkuvaa työtä vas-tuullisuuden parantamiseksi. Tutkimuksen tuloksia voidaan käyttää kuluttajien tietoisuuden lisäämiseen vastuullisuudesta ja ympäristöjohtamisesta. Perustuen tutkimuksessa esiin tulleisiin asioihin, erityyppiset vastuullisuudesta kertovat tiedot voidaan paremmin kohdentaa tunnistettuihin kohderyhmiin. Nämä tulokset auttavat yrityksiä myös ennustamaan vastuullisuuden vaikutusta kuluttajakäyttäytymiseen.
Keywords: sustainable development; environmental management; food industry; consumer behaviour; kestävä kehitys; ympäristöjohtaminen; elintarviketeollisuus; kuluttajakäyttäytyminen; fi=Tuotantotalous (kauppatieteet)|en=Industrial Management|; Master's Programme in Industrial Management